Electrochemical corrosion behavior of passivated precipitation hardening stainless steels for aerospace applications - Villegas Tovar, José Miguel; Gaona Tiburcio, Citlalli; Lara Banda, María del Refugio; Maldonado Bandala, Erick; Baltazar Zamora, Miguel Ángel; Cabral Miramontes, José Ángel; Nieves Mendoza, Demetrio; Olguín Coca, Javier; Estupiñan López, Francisco Humberto; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2023)
Precipitation-hardening (PH) stainless steels (SS) are widely used in various aerospace applications. These steels exhibit good mechanical and corrosion resistance. The electrochemical behavior of 15-5PH, 17-4PH, Custom450 and AM 350 stainless steels passivated with citric and nitric acid baths for 60 and 90 min at 25 and 49 °C were evaluated in 5 wt.% sodium chloride (NaCl) and 1 wt.% sulfuric acid (H2SO4) solutions. The electrochemical behavior was studied with potentiodynamic polarization curves (PPC) according to the ASTM G5-13 standard. The results indicated that there are two characteristic mechanisms that are present in the potentiodynamic polarization curves. When the PHSS is immersed in an H2SO4 solution, there is a secondary passivation, and in the NaCl solution, there is a pseudo-passivation (not stable passivation film). The current densities in the NaCl solution were between 10−4 and 10−5 mA/cm2, while those of H2SO4 were recorded around 10−2 and 10−3 mA/cm2. Citric acid does work as a passivating solution, and in some cases, the corrosion resistance of the stainless steel was comparable to that of nitric acid.